Atuação antirracista na biblioteconomia: uma incursão nas ações promovidas pelo CRB-8 - Caldeira, Bruno Rafael (Universidade Federal de São Carlos, 2022)
Considering the importance of combating racial inequalities by librarians, the question is how are racial issues guided in the actions and political agendas of the country's Regional Councils of Librarianship in favor of an anti-racist professional performance? In this sense, we seek to analyze in the Strategic Plans of the CRB-8 proposals that favor and contribute to an anti-racist professional performance on the part of the librarian, in order to identify the degree of commitment of these managements to a more politicized, egalitarian and diverse Librarianship, having scope of racial issues. Therefore, it conducts an exploratory and descriptive research, through bibliographic research and survey, analyzing the Strategic Plans of the last ten years of the CRB-8. As a result, it appears that the actions and political agendas of the CRB-8 in favor of an anti-racist professional performance are limited and are not explicitly presented in the respective documents. It is concluded that the theme needs greater involvement on the part of the CRB-8, making it opportune to conduct broader studies that observe how these actions are inserted in the other Councils in Brazil.
Anti-racist action in librarianship: a foray into the actions promoted by the CRB-8
Keywords: Biblioteconomia; Bibliotecário; Atuação antirracista; CRB-8; Planejamento estratégico; Librarianship; Librarian; Anti-racist action; Strategic planning; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA